Equalizing rural health professionals' information access: lessons from a follow-up outreach project. - Dorsch, J L (1997)
A follow-up outreach project was undertaken to extend and reinforce the work of a National Library of Medicine-funded outreach project conducted in west central Illinois in 1991. The participants included five of the eight original sites as well as additional populations. An evolving partnership with the state's Center for Rural Health expanded the project's geographic area statewide. Evaluation showed benefits of varied training formats, reexposure to end-user searching, and the importance of "readiness." Follow-up training and longer trials for practice searching resulted in greater volume of search and document delivery activity. Varied training formats proved successful in reaching specific groups. Loansome Doc activity throughout the eighteen-month project suggested sustained use of Grateful Med beyond the two-month trial periods. The introduction of Grateful Med/Loansome Doc to unaffiliated health professionals is an important component in equalizing information access. Future information service initiatives are suggested to meet the challenge of building a rural information infrastructure and support system for health professionals.